Further evidence for the involvement of kinin in anaphylactic shock in the rat - Starr, M. S. (1969)
1. Sodium phenylbutazone, soya bean trypsin inhibitor, or the concomitant administration of ascorbic acid and mepyramine protected rats against anaphylactic shock at 10 days after sensitization but gave no protection against anaphylaxis at 20 days. 2. During anaphylactic shock in rats at 10 days after sensitization, the plasma bradykinin and bradykininogen levels, as well as those in the intestinal lumen and peritoneal cavity, were markedly raised. 3. The results support the hypothesis that there are two phases in anaphylaxis in the rat—an early phase in which bradykinin is a mediator and against which phenylbutazone or soya bean trypsin inhibitor or the mixture of ascorbic acid and mepyramine, give protection, and a late phase which does not involve bradykinin.